Awareness about Newly Launched Social Security Schemes among Rural Population in India - Vidhate, Kshama B; Kundap, Ritesh (National Journal of Community Medicine, 2016)
Introduction: Utilization of social security schemes by the rural population has never been assessed in India. Awareness of these schemes play a crucial role in their utilization. This study was conducted to assess the awareness about newly launched social security schemes among rural population and give recommendations based on study findings. Methods: A sample of 150 individuals in the field practice area of a medical college were subjected to a questionnaire regarding awareness of recently launched 4 social security schemes - Sukanya Samridhi Yojana, Pradhan Mantri Suraksha Bima Yojana, Atal Pension Yojana, and Pradhan Mantri Jeevan Jyoti Bima Yojana. Results: In the study, 76% were aware of any one of the recently launched social security schemes, of which 44% registered for any one of these schemes. Conclusion: The awareness of the rural people regarding the newly launched social security schemes was high and is affected by the age, gender, literacy status and socioeconomic class of the people.